Agencies and the Politics of Agencification in Hungary - György HAJNAL (Transylvanian Review of Administrative Sciences, 2011)
The article pursues two related ambitions. Firstly, it seeks to give an overarching view of post-transition Hungary’s agency field by giving a qualitative description and analysis of the development of the legal-institutional framework, and by characterizing the proliferation of agencies with quantitative information. Secondly, and more specifically, the article explores certain aspects of agencies’ politicization; in particular, it seeks to identify the extent to which central governmental policies related to agencies serve the latent function of strengthening political control over agencies. The analysis corroborates the results of an earlier, more limited one: the hypothesis regarding the existence of such political control functions is supported by the empirical evidence.